2021
DOI: 10.1101/2021.08.02.454800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alternative oxidase1a and 1d limit proline-dependent oxidative stress and aid salinity recovery in Arabidopsis

Abstract: A link between Pro catabolism and mitochondrial reactive oxygen species production has been established across eukaryotes and in plants increases in leaf respiration rates have been reported following Pro exposure. Here we investigated how alternative oxidases (AOXs) of the mitochondrial electron transport chain accommodate the large, atypical flux resulting from Pro catabolism and limit oxidative stress during Pro breakdown in mature Arabidopsis leaves. Following Pro treatment, AOX1a and AOX1d accumulate at t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…Specific effects of the lack of AOX1a on photosynthetic efficiency have been investigated at mechanistic depth ( Bartoli et al, 2005 ; Dahal et al, 2015 ; Dahal and Vanlerberghe, 2017 , 2018 ), while observations of AOX1a-related phenotypes under biotic or salt stress have been more loosely linked to the modulation of mitochondrial ROS production ( Smith et al, 2009 ; Vishwakarma et al, 2015 ; Dahal and Vanlerberghe, 2017 ). Even though the AOX mode of function supports the idea of a platform role in alleviating mETC flux impairment and maintaining cellular redox balance across a broad range of developmental and environmental fluctuations ( Van Aken et al, 2009 ; Selinski et al, 2018 ; Florez-Sarasa et al, 2020 ; Vanlerberghe et al, 2020 ; Wang et al, 2020 ), the phenotypes associated with the genetic impairment of AOX function in vivo have been remarkably mild, and limited to specific growth regimes ( Giraud et al, 2008 ; Strodtkötter et al, 2009 ; Kühn et al, 2015 ; Oh et al, 2021 ). Consistent with these mild and specific effects, a range of treatments that we used to induce acute stress at the seedling level did not lead to any obvious phenotypic difference ( Supplemental Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific effects of the lack of AOX1a on photosynthetic efficiency have been investigated at mechanistic depth ( Bartoli et al, 2005 ; Dahal et al, 2015 ; Dahal and Vanlerberghe, 2017 , 2018 ), while observations of AOX1a-related phenotypes under biotic or salt stress have been more loosely linked to the modulation of mitochondrial ROS production ( Smith et al, 2009 ; Vishwakarma et al, 2015 ; Dahal and Vanlerberghe, 2017 ). Even though the AOX mode of function supports the idea of a platform role in alleviating mETC flux impairment and maintaining cellular redox balance across a broad range of developmental and environmental fluctuations ( Van Aken et al, 2009 ; Selinski et al, 2018 ; Florez-Sarasa et al, 2020 ; Vanlerberghe et al, 2020 ; Wang et al, 2020 ), the phenotypes associated with the genetic impairment of AOX function in vivo have been remarkably mild, and limited to specific growth regimes ( Giraud et al, 2008 ; Strodtkötter et al, 2009 ; Kühn et al, 2015 ; Oh et al, 2021 ). Consistent with these mild and specific effects, a range of treatments that we used to induce acute stress at the seedling level did not lead to any obvious phenotypic difference ( Supplemental Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, capacity from other AOX isoforms is usually insufficient for compensation in Arabidopsis seedlings. Interestingly, a recent study found that AOX1d can compensate for absence of AOX1a under specific metabolic conditions such as high rates of proline catabolism, as physiologically occurring during recovery from salinity stress ( Oh et al, 2021 ). In aox1a seedlings, DTT treatment led to a similar phenotype of impaired root growth as for AA, suggesting mETC capacity became limiting for the dissipation of thiol-mediated reductive stress in the absence of AOX1a.…”
Section: Discussionmentioning
confidence: 99%